Government Employee with Work Agreement (PPPK) Position and Regulation in Staffing System based on Civil Servant Act - Novita Sebtianingsih, Amaranda; Iskandar Ichlas, Rudy; Nashriany Jufri, Nur (LPPM Universitas Ekasakti Padang, 2024)
One of the key aspects of this reform is the restructuring of the staffing system, which includes the management of human resources in the public sector. However, the implementation and technical arrangements regarding PPPK still face various challenges, especially related to the position in the overall staffing system. This study uses a normative juridical method with a qualitative approach with a literature study. The position of PPPK and State Civil Apparatus (ASN) is regulated by Law of the Republic of Indonesia Number 20 of 2023 concerning State Civil Apparatus. Arrangements that have been stipulated by laws and regulations related to PPPK include 1) Law of the Republic of Indonesia Number 20 of 2023 concerning the State Civil Apparatus. 2) Government Regulation Number 49 of 2018 concerning PPPK Management. 3) Ministerial Regulation of PAN-RB Number 2 of 2019 concerning PPPK Procurement. Equal Rights and Obligations are PPPK and civil servants entitled to receive salaries and allowances in accordance with applicable regulations. In contrast, PPPK is appointed to fill certain positions without a fixed career path, although they can change positions through re-selection or promotion based on performance.